Characterization of the Skid Resistance and Mean Texture Depth in a Permeable Asphalt Pavement - Afonso, Márcia Isabel Lopes (2020)
Road pavements need a deep characterization of the surface layer, with which the vehicles have direct contact and, therefore, must provide security to the users. The use of permeable asphalt pavements (PAP) with porous layers has provide obvious advantages in reducing runoff and the rainwater infiltration into the soil or for storage. However, the study of the interaction between the pavement surface layer and the tire rubber requires additional tests in terms of texture and friction, since they are important parameters for the design, construction, management, maintenance and roads safety. Considering the application of a PAP in a parking lot, the study objective was to characterize in the field the pavement surface in terms of mean texture depth (MTD) and skid resistance (Pendulum test value, PTV). The methods used were the volumetric technique by the patch test and the pendulum test, according to EN 13036-1 and EN 13036-4, respectively. The double layer porous asphalt (DLPA) at the surface is characterized by having a structure with high voids content that led to results of clearly rougher macrotexture and good skid resistance. The normalized limit values were met, however, a very strong correlation between MTD and PTV was not observed. A comparison was also made with porous surfaces of other studies and it was found that porous asphalt has a good behaviour at the start of construction which may tend to improve in the long term. From the study, it is concluded that the PAP presents good performance of the surface layer, providing road safety to users.